Microscopic Malaria Infection and Its Determinants in Urban and Rural Populations Living in South-East Gabon - Jean-Claude Biteghe-Bi-Essone; Roméo Karl Imboumy-Limoukou; Steede-Seinnat Ontoua; Nick Atiga; Nancy Mbani-Mpega; Lady Charlène Kouna; Jean Bernard Lekana-Douki; Lydie Sandrine Oyegue-Liabagui (Journal of Parasitology Research)
A better understanding of malaria epidemiology in both asymptomatic and symptomatic individuals is essential for developing strategies to control the disease. This study was conducted to determine Plasmodium infection prevalence and its associated factors among people living in Franceville (urban area) and in the villages of Pana and Mvengue (rural areas) in south-east Gabon between April and July 2022. This cross-sectional study was conducted among all consenting residents of Franceville, Mvengue, and Pana between April and July 2022. After obtaining informed consent, Plasmodium sp. infection was screened by microscopy, and a structured questionnaire was developed to record sociodemographic data, attitudes, and practices regarding malaria. A total of 976 participants were included, with 491 in urban areas and 485 in rural areas. The overall prevalence of Plasmodium sp. infection was 21.62% (211/976; 95% confidence interval (CI) [19.15–24.31]). The prevalence was highest in children aged 6–11 years. In urban areas, the prevalence was 19.35% (95/491; 95% CI [16.10–23.07]), and 96.84% of infections were asymptomatic. The most infected age group was 18–23 years. In rural areas, the prevalence was 23.92% (116/485, 95% CI [20.34–27.91], and 93.97% (109/116) of infections were asymptomatic. Socioeconomic characteristics, attitudes, and practices towards Plasmodium sp. infection were not associated with a risk of asymptomatic malaria infection. This study highlights the importance of asymptomatic Plasmodium sp. infection in south-east Gabon and the need for control strategies adapted to different areas and age groups. Detection and treatment of asymptomatic carriers could be an important lever for malaria control and elimination in the country.